2003
DOI: 10.1007/s11894-003-0048-0
|View full text |Cite
|
Sign up to set email alerts
|

Small bowel bacterial overgrowth: Presentation, diagnosis, and treatment

Abstract: Small bowel bacterial overgrowth (SBBO) syndrome is associated with excessive numbers of bacteria in the proximal small intestine. The pathology of this condition involves competition between the bacteria and the human host for ingested nutrients. This competition leads to intraluminal bacterial catabolism of nutrients, often with production of toxic metabolites and injury to the enterocyte. A complex array of clinical symptoms ensues, resulting in chronic diarrhea, steatorrhea, macrocytic anemia, weight loss,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
89
0
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(97 citation statements)
references
References 55 publications
3
89
0
4
Order By: Relevance
“…1 Attar et al compared the efficacy of three different agents for the treatment of bacterial overgrowth-related diarrhoea (amoxicillin-clavulanic acid, norfloxacin and Saccharomyces boulardii) showing that stools declined by 29% and 45% with amoxicillin-clavulanic acid and norfloxacin, yet negative H 2 breath test percentages were 50% and 30%, respectively. 10 A recent study by…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Attar et al compared the efficacy of three different agents for the treatment of bacterial overgrowth-related diarrhoea (amoxicillin-clavulanic acid, norfloxacin and Saccharomyces boulardii) showing that stools declined by 29% and 45% with amoxicillin-clavulanic acid and norfloxacin, yet negative H 2 breath test percentages were 50% and 30%, respectively. 10 A recent study by…”
Section: Discussionmentioning
confidence: 99%
“…Current SIBO treatment is based on empirical courses of broad spectrum antibiotics as few controlled studies with respect to choice and duration of antibiotic therapy exist at present. 1 A remarkable improvement in symptoms can be achieved in most patients. 1 Overgrowth may occur either by a mix of aerobic and anaerobic flora or by purely aerobic flora.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In health, the summated actions of gastric acid, peristalsis, intestinal fluid, antibacterial proteins, and the ileocecal valve keep the quantity of bacteria in the small intestine at low levels. Failure of any of these mechanisms can lead to small intestinal bacterial overgrowth (SIBO), a syndrome that can result in diarrhea, abdominal distension, flatulence, steatorrhea, macrocytic anemia, and weight loss (Singh and Toskes 2003). Weight loss may result from bacterial competition for ingested nutrients, intestinal inflammation from enterotoxic metabolites, and the ability of bacteria to deconjugate bile acids, thus reducing their ability to emulsify fat (Hofmann and Mysels 1992).…”
Section: Microbial Dysbiosismentioning
confidence: 99%
“…The pathophysiology of IBS is not clear and various hypotheses have been suggested, such as alterations in the intestinal microbiota, dysfunction of the gut-brain axis & autonomic nervous system, genetic predisposition, visceral antipathy, altered gastrointestinal hormones and obesity (12,13). Various studies have indicated an association of increased intestinal bacteria with IBS and increased permeability of the intestine (14,15). Intestinal permeability may be increased in the high fat diet of obesity (16).…”
Section: Introductionmentioning
confidence: 99%